The volleyball setter`s decision-making on attacking - Alvares Denardi, R.; Romero Clavijo, F. A.; Costa de Oliveira, T. A.; Travassos, B.; Tani, G.; Corrêa, U. C. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to investigate the volleyball setter`s decision-making on tipping, based on spatiotemporal variables of interaction between players and between players and the game environment. The sample consisted of 172 sequences of 20 volleyball games from 6 male and 10 female teams. The actions selected for analysis were 86 tips and 86 sets (control group), both made by the setters. From the players` x and y coordinates of displacement trajectory, 37 spatiotemporal measures of players` interaction were calculated as dependent variables, which were analysed by multivariate analysis of variance. Results showed that tips and sets differed in terms of (i) final area between opponents, (ii) displacement of setter to reach the ball, (iii) displacement velocity of setter to reach the ball, (iv) distance between setter and net in the initial moment, (v) distance between setter and net in the final moment, (vi) pass velocity and (vii) final distance between setter and blockers. It was concluded that these variables formed a spatiotemporal configuration of the game that influenced the setter`s decision-making on tipping.